Pendidikan Karakter Berbasis Pendidikan Kewarganegaraan di Era Society 5.0: Systematic Literature Review (SLR) terhadap Tantangan dan Implementasi - Hanifah Hanifah; Dewa Bagus Sanjaya; I Nengah Suastika (JPDI (Jurnal Pendidikan Dasar Indonesia), 2025)
This study aims to analyze the role of character education based on Civic Education (PKn) in the era of Society 5.0, focusing on its implementation challenges and strategies. Using the Systematic Literature Review (SLR) approach, this study examines a variety of literature relevant to the topic. The results of the study show that character education in PKn plays an important role in shaping students' morals, civic awareness, and social values. However, the main challenge faced is the negative influence of digital technology on student morality, as well as the lack of integration between schools, families, and society in instilling character values consistently. Therefore, strategies that can be applied include the integration of technology in learning, contextual approaches based on local wisdom, and strengthening collaboration between schools, families, and communities. This study concludes that character education in PKn must adapt to technological developments to ensure that the nation's character is maintained in the digital era.